Optimalisasi Pariwisata dan Olahan Pasca Panen Sektor Perkebunan Desa Jrahi Kabupaten Pati yang Berkelanjutan menuju Desa Mandiri - Isti Mulyawati; Umar Hidayat; Moch Faizal Rachmadi; Margareta Rahayuningsih; Fafurida Fafurida; Danang Dwi Saputro (PADMA, 2025)
Jrahi Village is a highland area located in Gunungwungkal District, Pati Regency. Jrahi Village boasts abundant tourism potential and a diverse range of natural resources, including plantations of durian, avocado, coffee, banana, and others. However, limited capabilities, knowledge, and skills pose a barrier to integrating and optimizing the potential of the tourism and plantation sectors. The implementation method used is outreach, training, technology application, mentoring, evaluation, and program sustainability. The results of the community service program include increasing awareness of sustainable tourism management based on conservation and biodiversity preservation, creating a disaster mitigation system, and enhancing human resource competency. Furthermore, the creation of a Micro-Hydro Power Plant is also an effort to intensify green energy innovation. The community is also assisted in processing the plantation sector to be more competitive, innovating product diversification, redesigning packaging, and other efforts.